Correlates of maternal health services utilization among adolescent mothers in Ghana: analysis of Ghana maternal health survey 2017 - Anita Anima Daniels; Emmanuel Anongeba Anaba; Obed Ernest A. Nettey (BMC Pregnancy and Childbirth)
Abstract Background The prevalence of adolescent pregnancy is high in developing countries and poses a public health threat. This study aimed to assess the coverage and correlates of optimal ANC visits, early initiation of ANC visits, assisted delivery and health facility delivery among adolescent mothers. Methods We analysed data from the 2017 Ghana Maternal Health Survey (GMHS), using a sample of 567 (weighted) and 527 (unweighted) adolescent mothers with at least one live birth or stillbirth in the five (5) years preceding the survey. Results Most participants obtained four or more ANC visits, accessed health facility delivery and assisted delivery. Half (50%) of the participants initiated ANC visits in the first trimester. Less than half (39%) of the participants utilized all four maternal health services optimally. Utilization of maternal health services was associated with predisposing factors (age and parity) and enabling factors (wealth index, health insurance, permission to seek care). For instance, adolescent mothers aged 18–19 years (AOR = 1.65, 95% CI: 1.01–2.70) had increased odds of early initiation compared to those aged 15–17 years. Adolescent mothers who were uninsured (AOR = 0.30, 95% CI: 0.15–0.63) were less likely to obtain optimal ANC visits than insured mothers. Adolescent mothers in the middle wealth index (AOR = 1.97, 95% CI: 1.06–3.63) were about twice more likely to utilize all the four maternal health services compared to those in the lowest wealth index. Conclusion This study has demonstrated that adolescent utilization of ANC visits, health facility delivery and skilled delivery were satisfactory. However, ANC initiation and optimal utilization of the recommended maternal health services were unsatisfactory. Utilization of the maternal health services was determined by predisposing factors such as age and parity as well as enabling factors including health insurance coverage, permission for treatment and wealth index.